y = 17.5 when x = 5
Step-by-step explanation:
When two variables are in direct proportion i.e. change in one variable causes change in other variable it can be expressed mathematically as:
y∝x
when the proportionality symbol is removed a proportionality constant is introduced
So,
[tex]y = kx[/tex]
Putting y = 7 and x = 2
[tex]7 = k * 2\\k = \frac{7}{2}\\k = 3.5[/tex]
So the expression will be:
[tex]y = 3.5x[/tex]
Now putting x = 5
[tex]y = 3.5 * 5\\y = 17.5[/tex]
Hence,
y = 17.5 when x = 5
Keywords: Proportion, variables
Learn more about proportion at:
brainly.com/question/3306327brainly.com/question/3375830#LearnwithBrainly
Find a quadratic function that includes the set of values below.
(0,9). (2,15) (3,12)
Answer:
[tex]f(x) = -2x^2 + 7x + 9[/tex]
Step-by-step explanation:
[tex]f(x) = ax^2 + bx + c\\f(0) = 9 => c = 9;\\f(2) = 15 = 4a + 2b + 9 <=> 2a + b = 3\\f(3) = 9a + 3b + 9 = 12 <=> 3a + b = 1\\Subtract the second equation from the first:\\-a = 2 => a = -2; b = 7; c = 9\\f(x) = -2x^2 + 7x + 9[/tex]
To find a quadratic function, substitute each given coordinate into the equation and solve the resulting system of equations.
Explanation:To find a quadratic function, we need to use the form y = ax^2 + bx + c. From the given set of values, we can substitute each coordinate (x, y) into the equation to get three different equations. So:
When x = 0, y = 9, we get: 9 = a(0)^2 + b(0) + c, which simplifies to c = 9.When x = 2, y = 15, we get: 15 = a(2)^2 + b(2) + 9, which simplifies to 4a + 2b = 6.When x = 3, y = 12, we get: 12 = a(3)^2 + b(3) + 9, which simplifies to 9a + 3b = 3.Now we have a system of equations that we can solve simultaneously. Solving the second and third equations using any appropriate method, we find that a = -1 and b = 5.
Therefore, the quadratic function that includes the given set of values is y = -x^2 + 5x + 9.
Learn more about Quadratic Functions here:https://brainly.com/question/35505962
#SPJ2
Jose's banquet hall charges a one time fee of $100 plus $50 per guest for weddings. Another wedding venue, Palace of Aaron, Charges a one-time fee of $200 in addition to $45 per guest. Letting "g" represent the number of wedding guests, Write an algebraic expression to represent the cost of renting each of the banquet halls.
(First part)
(Second part)
At how many wedding guests is the cost the same for both venues? Show your work.
Answer:
Part 1:
Jose's Banquet Hall: 50g+100
Palace of Aaron: 45g+200
Part 2:
20 guests
Step-by-step explanation:
Part 1:
$50 per guest plus $100 fee
50g+100
$45 per guest plus $200 fee
45+200
Part 2:
$50(20)+$100=$1100
$45(20)+$200=$1100
Answer:
II. [tex]\displaystyle 20\:wedding\:guests[/tex]
I. [tex]\displaystyle 100 + 50g = 200 + 45g[/tex]
Step-by-step explanation:
100 + 50g = 200 + 45g
- 200 - 50g - 200 - 50g
___________________
[tex]\displaystyle \frac{-100}{-5} = \frac{-5g}{-5} \\ \\ 20 = g[/tex]
So, at twenty wedding guests, the cost will balance for both venues.
I am joyous to assist you anytime.
What does x equal if x-10 divided by x-4 equals 50 divided by -6
Answer:
x=65/14
Step-by-step explanation:
(x-10)/(x-4)=50/-6
-50/6=-25/3
(x-10)/(x-4)=-25/3
x-10=-25/3(x-4)
x-10=-25/3x+100/3
x-(-25/3x)=100/3+10
x+25/3x=130/3
28/3x=130/3
x=(130/3)/(28/3)
x=(130/3)(3/28)
x=130/28
x=65/14
Molly is having her birthday party at Pizza Party Palace. The costs involved are listed below. Pizza Party Palace requires a 10% deposit prior to the date of the event. If the deposit has been paid, how much is still owed for Molly's party?
The right answer is Option D.
Step-by-step explanation:
Given,
Food and Drinks = $200
Game tokens = $100
Other = $60
Total amount = 200+100+60 = 360
Deposit = 10%
Deposit amount = 10% of total amount
[tex]Deposit\ amount=\frac{10}{100}*360\\Deposit\ amount=\frac{3600}{100}\\Deposit\ amount= \$36[/tex]
Amount left to be paid = Total amount - deposit amount
Amount left to be paid = [tex]360-36=\$324[/tex]
$324 is still owed for Molly's party.
The right answer is Option D.
Keywords: Percentage, subtraction
Learn more about subtraction at:
brainly.com/question/10081622brainly.com/question/10341324#LearnwithBrainly
A 2-column table has 4 rows. The first column is labeled x with entries negative 2, negative 1, 0, 1. The second column is labeled f (x) with entries 0.004, 0.02, 0.1, 0.5.
What is the growth factor of the exponential function represented by the table?
0.2
0.1
5
20
Answer:
5
Step-by-step explanation:
take 0.5 divided by 5 and it gives you your next number on the chart:)
Answer: 5
Step-by-step explanation:
The growth factor of the exponential function is the ratio of the two consecutive terms (y-values).
i.e. Growth factor = [tex]b=\dfrac{y(x_2)}{y(x_1)}[/tex]
As per given , we have table
x y
-2 0.004
-1 0.02
0 0.1
1 0.5
Then, for [tex]x_1=-2[/tex] and [tex]x_2=-1[/tex] the growth factor of the exponential function represented by the table would be :
[tex]b=\dfrac{y(-1)}{y(-2)}=\dfrac{0.02}{0.004} =5[/tex]
Hence, the growth factor of the exponential function represented by the table is 5 .
PLEASE HELP ASAP:))))))))!!!!!!!!!!!!
Which of the following purchases shows the LEAST expensive unit price?
Group of answer choices
A 4 pack of t-shirts for $2.24
A 3 pack of t-shirts for $3.00
An 8 pack of t-shirts for $4.24
A 6-pack of t-shirts for $3.12
Answer:
6-pack for 3.12
Step-by-step explanation:
Find unit price
2.24/4=0.56
3.00/3=1
4.24/8=0.53
3.12/6=0.52
Passes through (-1,4) and has a slope of 4
Answer:
y-4=4(x+1)
Step-by-step explanation:
y-y1=m(x-x1)
m=4
y-4=4(x-(-1))
y-4=4(x+1)
Answer: equation = y=4x+8
Step-by-step explanation:
y=mx+b
4=4(-1)+b
b=8
equation = y=4x+8
The highest mountains in the world are the Himalayas, at the border between the Indian and Eurasian plates. The Himalayas formed in a ________________.
A. subduction zone
B. divergent boundary
C. collision zone
D. transform boundary
Answer: collision zone
Step-by-step explanation:As a result of this collision, the sedimentary rocks which were settled in the large-scale depression in the Earth's crust called Tethys were folded and formed the Himalayas.
C collision zone
The Himalayas are the world's highest mountains, straddling the Indian and Eurasian plates. The Himalayas were formed by a collision zone.
What is meant by collision zone?A collision zone occurs when two tectonic plates with continental lithosphere collide at a convergent boundary. A collision zone occurs when two tectonic plates with continental lithosphere collide at a convergent boundary. Because continental lithosphere is rarely subducted due to its low density, the result is a complex orogeny involving folding and thrust faulting as blocks of continental crust pile up above the subduction zone. This includes the collision zone in Eastern Anatolia. Tropical Asia is a hotspot for plate collisions between the northward-drifting Australian plate and plates from the Pacific and the Asian mainland. As a result, the area is mountainous and shaped by shear zones and volcanism. as well as the Banda Arc-Australian collision zoneTo learn more about collision zone, refer to:
https://brainly.com/question/15068707
#SPJ2
If 4 + 6 = 10, does (4 + 6) X 3 = 10 x 3? Why
or why not?
Answer:
yes.
Step-by-step explanation:
because I did the work and 10 times 3 equals 30 and 4 plus 6 times 3 equals 30.
Answer:
Yes because L.H.S = R.H.S
Step-by-step explanation:
4 + 6 = 10
(4 + 6) X 3
=> 10 X 3
=> 30
ts Graph the line whose x-intercept is 5 and whose y-intercept is 3
Answer:
The equation of line whose x-intercept is 5 and whose y-intercept is 3
is given as 5 y + 3x = 15.
Step-by-step explanation:
Here, the given x - intercept = 5.
⇒ The point on the given equation is (x,0) = (5,0)
And, the y- intercept is given as 3
⇒ The point on the given equation is (0,y) = (0,3)
So, the two points given on the equation of line is A(5,0) and B(0,3)
Now, the slope of the line equation [tex]m = \frac{y_2 - y_2}{x_2-x_1}[/tex]
So, here the slope of line AB is [tex]m = \frac{3- 0}{0-5} = -\frac{3}{5}[/tex]
Now by POINT SLOPE FORMULA:
The equation of a line with point (x0,y0) and slope m is given as:
(y- y0) = m (x-x0)
⇒The equation of line AB is given as
[tex]( y - 0) = -\frac{3}{5} (x -5)\\\implies 5 y = -3x + 15\\\implies 5 y + 3x = 15[/tex]
Hence, the equation of line AB is given as 5 y + 3x = 15.
What is the factored form of the quadratic expression x^2+36
Answer:
(x − 6i) (x + 6i)
Step-by-step explanation:
Using real numbers, x² + 36 is already simplified.
Using imaginary numbers:
x² + 36
x² − 36i²
(x − 6i) (x + 6i)
13 + 2k = 3k + 4(k - 3)
Answer:
k=5
Step-by-step explanation:
7
k
−
12
=
13
+
2
k
Move all terms containing
k
to the left side of the equation.
Which value satisfies the inequality 5x + 7 ≤ 8x - 3 + 2x?
A) -2
Eliminate
B) -1
C) 0
D) 2
Answer:
D) 2
Step-by-step explanation:
5x + 7 [tex]\leq[/tex] 8x -3 +2x
5x + 7 [tex]\leq[/tex] 10x - 3
7 + 3 [tex]\leq[/tex] 10x - 5x
10 [tex]\leq[/tex] 5x
2[tex]\leq[/tex] x
x[tex]\geq[/tex]2
If y varies inversely as the square of x and y=2 when x=4.Find x when y=4/5
Answer:
hnjmmm
Step-by-step explanation:
m,,\
l;'
Answer:
x = 2[tex]\sqrt{10}[/tex]
Step-by-step explanation:
Given that y varies inversely as the square of x then the equation relating them is
y = [tex]\frac{k}{x^2}[/tex] ← k is the constant of variation
To find k use the condition y = 2 when x = 4
k = yx² = 2 × 4² = 2 × 16 = 32
y = [tex]\frac{32}{x^2}[/tex] ← equation of variation
When y = [tex]\frac{4}{5}[/tex], then
[tex]\frac{4}{5}[/tex] = [tex]\frac{32}{x^2}[/tex] ( cross- multiply )
4x² = 160 ( divide both sides by 4 )
x² = 40 ( take the square root of both sides )
x = [tex]\sqrt{40}[/tex] = [tex]\sqrt{4(10)}[/tex] = 2[tex]\sqrt{10}[/tex]
Tomas buys a bag of 5 peaches for $3.55. Write and solve an equation to find how much money, m, Tomas paid for each peach
Answer:
Step-by-step explanation:
$3.55 ÷ 5 = .71 each peach
To find out how much Tomas paid for each fruit, we set up the equation m = $3.55 / 5, which when solved gives m = $0.71. This means that Tomas paid $0.71 for each peach.
Explanation:To find out how much Tomas paid for each peach, you can set up an equation. Because Tomas buys 5 peaches for $3.55 in total, you can express this as a simple division. To solve the equation, divide $3.55 (total cost) by 5 (total number of peaches).
So, the equation would be m = $3.55 / 5.
Solving this equation gives: m = $0.71. Therefore, Tomas paid $0.71 for each peach.
Learn more about Cost per Peach here:
https://brainly.com/question/31009245
#SPJ3
Kenny had 35 baseball cards in his collection last year. This year he has 20% more baseball cards. Kenny sold 8 of his baseball cards for extra money. How many baseball cards does Kenny have after he sold 8 for extra money? Show Work!
(A) 7 baseball cards left
(B) 34 baseball cards left
(C) 35 baseball cards left
(D) 42 baseball cards left
The right answer is Option B.
Step-by-step explanation:
No. of baseball cards = 35
Increase = 20%
Number of increased cards = 20% of 35
[tex]Increased\ cards = \frac{20}{100}*35\\Increased\ cards=\frac{700}{100}\\Increased\ cards=7[/tex]
Total cards = 35+7 = 42
No. of cards sold = 8
Cards left = Total cards - No. of cards sold
[tex]Cards\ left=42-8\\Cards\ left=34[/tex]
The right answer is Option B.
Keywords: Addition, subtraction
Learn more about addition at:
brainly.com/question/8902155brainly.com/question/8955867#LearnwithBrainly
find the solution of this system of equations. -x - 5y= 30, 10x + 5y= -75
Answer:
x=-5, y=-5. (-5, -5).
Step-by-step explanation:
-x-5y=30
10x+5y=-75
-----------------
9x=-45
x=-45/9
x=-5
-(-5)-5y=30
5-5y=30
5y=5-30
5y=-25
y=-25/5
y=-5
Need help with geometric sequences
30 points
Answer:
[tex]a_{n}[/tex] = 6[tex](5)^{n-1}[/tex]
Step-by-step explanation:
The n th term of a geometric sequence is
[tex]a_{n}[/tex] = a[tex](r)^{n-1}[/tex]
where a is the first term and r the common ratio
Here a = 6 and r = 30 ÷ 6 = 5, thus
[tex]a_{n}[/tex] = 6[tex](5)^{n-1}[/tex]
PLEASE HELP ME I don’t know the answer
Answer:
7 and 8 would work
Step-by-step explanation:
just insert them as w and they have to be greater than 20. I hope this helps.
Answer:
7 and 8
Step-by-step explanation:
Solving the inequality
5w - 10 > 20 ( add 10 to both sides )
5w > 30 ( divide both sides by 5 )
w > 6
The only values from the solution set greater than 6 are
7 and 8
if 3x - y = 3 and -x + y = 3 then xy=___?
First find x and y.
Solve system of equations by elimination.
3x-y=3
+(-x+y=3)
---------------
2x=6
x=3
Now plug in x into one of the equations to find y.
-3+y=3
y=6
xy=3x6=18
Final answer:
The product of xy, given the system of equations 3x - y = 3 and -x + y = 3, is 18. This is found by first solving for x and y using the elimination method and then multiplying the obtained values.
Explanation:
To find the product of xy, we need to solve the system of equations given by 3x - y = 3 and -x + y = 3. Here we'll use the elimination method. Adding both equations together, we eliminate y:
3x - y + (-x + y) = 3 + 3
Which simplifies to:
2x = 6
Dividing both sides by 2, we get:
x = 3
To find y, we substitute x back into one of the original equations, for example, the second equation -x + y = 3:
-(3) + y = 3
-3 + y = 3
Adding 3 to both sides gives us:
y = 6
Now we can find the product of xy:
xy = 3 * 6
xy = 18
Therefore, the product of xy is 18.
3. Evaluate a + b for a = -46 and b= 34.
A:-12
B:80
C:-80
D:12
Answer:
A: -12Step-by-step explanation:
Put the values of a = -46 and b = 34 to the expression a + b:
-46 + 34 use the commutative property a + b = b + a
= 34 + (-46) = 34 - 46 = -12
The question is asking to evaluate the expression a + b, with a being -46 and b being 34. Evaluating the expression, we substitute the given values in to get -12. Therefore, the correct answer is A: -12.
Explanation:In algebra, when a question asks us to evaluate an expression, that simply means we need to substitute the given values into the equation and perform the operations to simplify it. In this problem, the expression is a + b, and the values given are a = -46 and b = 34.
To evaluate this, we substitute the given values in: (-46) + 34. When you add -46 and 34 together, you get a result of -12. Therefore, the correct answer is A: -12.
Learn more about Evaluate Expressionhttps://brainly.com/question/35337698
#SPJ2
Solve the system of equations: 2x + 3y = 13 x = 2 + 3y
2.3 is 46% of what number
Answer:
46% × 2.3 =
(46 ÷ 100) × 2.3 =
(46 × 2.3) ÷ 100 =
105.8 ÷ 100 =
1.058 ≈
1.06;
PLEASE HELP!!!!!!!! y+1=1/3(x−3) how do i graph this? what are the points?
Step-by-step explanation:
You have the equation of a line in the point-slope form:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
(x₁, y₁) - point on a line
Convert the given equation to the slope-intercept form:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept (0, b)
[tex]y+1=\dfrac{1}{3}(x-3)[/tex] use the distributive property
[tex]y+1=\dfrac{1}{3}x-1[/tex] subtract 1 from both sides
[tex]y=\dfrac{1}{3}x-2[/tex]
We only need two points to draw the line.
Choose two different x values. Put them in the line equation and calculate the y values:
for x = 0:
[tex]y=\dfrac{1}{3}(0)-2=0-2=-2\to(0,\ -2)[/tex]
for x = 3:
[tex]y=\dfrac{1}{3}(3)-2=1-2=-1\to(3,\ -1)[/tex]
A student in Greece discovers a pottery bowl
that contains 21% of its original amount of C-
14.
N = Noe-kt
No = inital amount of C-14 (at time t = 0)
N = amount of C-14 at timet
t = time, in years
k = 0.0001
age of the pottery bowl to the nearest year??
Answer:
The age of the pottery bowl to the nearest year is 15606 years.
Step-by-step explanation:
Let the initial amount of C-14 in the bowl i.e. [tex]N_{0} = 100[/tex] and today (say after t years) the amount of C-14 in the bowl i.e. N = 21.
Therefore, from the given equation we can write
[tex]21 = 100 e^{- 0.0001t}[/tex] {Since, k is give to be 0.0001}
⇒ [tex]0.21 = e^{- 0.0001t}[/tex]
Now, taking ln on both sides we get
ln 0.21 = - 0.0001t (ln e) {Since, [tex]\ln a^{b} = b \ln a[/tex]}
⇒ - 1.560647 = - 0.0001t {We have ln e = 1}
⇒ t = 15606.47 years ≈ 15606 years
Therefore, the age of the pottery bowl to the nearest year is 15606 years.(Answer)
7 2/15+52/3+9 13/15 a. 20 2/3 B.21 10/15 C.21 2/3 D.22 2/3 pls do i will mark brainlessness
Answer:
101/3 or 33 2/3
Step-by-step explanation:
7 2/15=107/15
9 13/15=138/15
107/15+52/3+138/15
107/15+138/15+52/3
245/15+52/3
245/15+260/15
505/15
simplify,
101/3
help will rate you 5 stars!!!!!!!!!
Answer:
first proof should be cpctc, second proof is the triangle sum theorem
6 identical sunglasses cost $420. What is the cost of one pair of sunglasses?
Answer:
One pair of sunglasses is $70
Step-by-step explanation:
Elsa is taking physical fitness tests in her strength training class. Each day, her results are compared to her results from previous days. The first day she completes a test is considered the baseline and is represented by 0. For instance, on the first day she did the flexibility test, her result was calculated as 0. On the second day, in comparison to her first day's result, she was able to reach 1/16inches less than the first day, which was recorded as - 1/16. Then, on the third day, Elsa recorded a result of -5/8.
A. On which day did Elsa reach farther: the second or third day?
B. By how much?
HELP ME D:
Answer:
A) The second day
B) 9/16 inches
Step-by-step explanation:
A) Elsa reached farther on the second day because -1/16 > -5/8
B) To calculate this we must first put both fractions above the same denominator. We can then subtract the smaller one from the bigger one:
-1/16 - (-10/16) = 9/16
Elsa reached 9/16 inches farther on the second day then she did on the first.
Final answer:
Elsa reached farther on the second day than the third day during her flexibility tests. She reached 9/16 inches farther on the second day compared to the third day.
Explanation:
Elsa is taking physical fitness tests in her strength training class where she tracks her progress by comparing her flexibility results to the baseline (first day). A negative value indicates she did not reach as far as the baseline.
A. On the second day, Elsa's flexibility test result was recorded as - 1/16 inches, and on the third day, it was -5/8 inches. Since -1/16 is greater than -5/8 (closer to zero), it means Elsa reached farther on the second day than the third day.
B. To find out by how much Elsa reached farther on the second day compared to the third day, we calculate the difference between the two measurements: (-1/16) - (-5/8) = 5/8 - 1/16. We must find a common denominator to subtract these fractions, which is 16. So we have (10/16) - (1/16) = 9/16 inches. Therefore, Elsa reached 9/16 inches farther on the second day compared to the third day.
What is the sum of the multiples of 3 between 100 and 1000
Answer:
165150 is the sum of the multiples of 3 between 100 and 1000.
Step-by-step explanation:
We need to find the sum of multiples of 3 between 100 and 1000.
First we will find the Total number of multiples of 3 between 100 and 1000.
Let a be the first multiple and l be the last multiple of 3
100 is not the multiple of 3.
101 is not the multiple of 3.
102 is the multiple of 3.
Hence first term a = 102
Similarly.
1000 is not a multiple of 3
999 is a multiple of 3
hence last term l = 999
Also d is the common difference.
hence d = 3.
Now by using Arithmetic progression formula we get;
[tex]T_n(l) =a+(n-1)d\\ 999=102+(n-1)3\\999-102=(n-1)3\\897=(n-1)3\\\frac{897}{3}=n-1\\\\n-1=299\\n=299+1\\n=300[/tex]
Hence there are 300 multiples of 3 between 100 and 1000
Now n=300, a=102, l = 999
Hence to find the sum of all the multiples we use the Sum of n terms in AP formula;
Sum of n term [tex]S_n= \frac{n}{2}(a+l)[/tex]
[tex]S_{300}= \frac{300}{2}(102+999)\\\\S_{300}= 150(102+999)\\S_{300}= 150\times 1101\\S_{300}= 165150[/tex]
Hence,165150 is the sum of the multiples of 3 between 100 and 1000.